2020
DOI: 10.1016/j.nicl.2020.102434
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow characteristics following hemodialysis initiation in older adults: A prospective longitudinal pilot study using arterial spin labeling imaging

Abstract: Highlights CBF declined approximately six months after hemodialysis initiation. The associations between longitudinal changes in 3MS score and regional CBF were observed. Decreased brain perfusion may contribute to the observed cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…The hippocampus plays an important role in cognitive memory and reasoning decisions [ 17 , 18 ]. Our results are consistent with those of previous studies [ 19 , 20 ]. For instance, Cheng BC et al used ASL to study CBF changes in ESRD patients on long-term peritoneal dialysis therapy and compared CBF in ESRD patients before and after peritoneal dialysis with that of HCs; they found that ESRD patients had a mean increase in CBF compared to HCs and that higher CBF in the left hippocampus of ESRD patients was associated with worse executive function [ 19 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The hippocampus plays an important role in cognitive memory and reasoning decisions [ 17 , 18 ]. Our results are consistent with those of previous studies [ 19 , 20 ]. For instance, Cheng BC et al used ASL to study CBF changes in ESRD patients on long-term peritoneal dialysis therapy and compared CBF in ESRD patients before and after peritoneal dialysis with that of HCs; they found that ESRD patients had a mean increase in CBF compared to HCs and that higher CBF in the left hippocampus of ESRD patients was associated with worse executive function [ 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…For instance, Cheng BC et al used ASL to study CBF changes in ESRD patients on long-term peritoneal dialysis therapy and compared CBF in ESRD patients before and after peritoneal dialysis with that of HCs; they found that ESRD patients had a mean increase in CBF compared to HCs and that higher CBF in the left hippocampus of ESRD patients was associated with worse executive function [ 19 ]. Li et al studied CBF changes in elderly adults before and after hemodialysis and found that global CBF within the gray matter and white matter was significantly higher in hemodialysis patients than in HCs, with significant local CBF increases in the hippocampus and orbitofrontal cortex [ 20 ]. These studies found CBF alterations in the hippocampus as we did, but the difference is that our study was conducted in patients with CKD4, which also suggests that alterations in CBF are already present in non-end-stage patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia, generally decreasing hemoglobin level, is common in HD patients. Relaxation time (T 1 ) of blood (T 1B ) varies with age and hematocrit or hemoglobin levels (11). CBF quantification results are significantly modified by the T 1B .…”
Section: Cerebral Blood Flow (Cbf) Calculationmentioning
confidence: 99%
“…To achieve rigorous CBF quantification, a singlecompartment model was used for CBF quantification (25). The hemoglobin levels of participants and the previously proposed general model were used to estimate the T 1B in this study (11,29). The hemoglobin levels of HD patients were derived from blood samples obtained during standard HD treatments; an age-and sex-dependent hemoglobin level was applied for HCs (30).…”
Section: Cerebral Blood Flow (Cbf) Calculationmentioning
confidence: 99%
See 1 more Smart Citation